A conceptual framework for rationalized and standardized Universal Newborn Hearing Screening (UNHS) programs. Issue 1 (December 2016) - Leo, Carlo; Mincarone, Pierpaolo; Sabina, Saverio; Latini, Giuseppe; Wong, John
Abstract Congenital hearing loss is the most frequent birth defect. The American Academy of Pediatrics and the Joint Committee on Infant Hearing established quality of care process indicators for Universal Newborn Hearing Screening starting from 1999. In a previous systematic review of Universal Newborn Hearing Screening studies we highlighted substantial variability in program design and in reported performance data. In order to overcome these heterogeneous findings we think it is necessary to optimize the implementation of Universal Newborn Hearing Screening programs with an appropriate application of the planning, executing, and monitoring, verifications and reporting phases. For this reason we propose a conceptual framework that logically integrates these three phases and, consequently, a tool (a check-list) for their rationalization and standardization. Our paper intends to stimulate debate on how to ameliorate the routine application of high quality Universal Newborn Hearing Screening programs. The conceptual framework is proposed to optimize, rationalise and standardise their implementation. The checklist is intended to allow an inter-program comparison by removing heterogeneity in processes description and assessment.